Equine Recurrent Uveitis: a review - KOMNENOU (Α. ΚΟΜΝΗΝΟΥ), A.; DIAKAKIS (Ν. ΔΙΑΚΑΚΗΣ), N.; DESIRIS (Α. ΔΕΣΙΡΗΣ), A. (Journal of the Hellenic Veterinary Medical Society, 2017)
Equine recurrent uveitis (ERU), also known as "periodic ophthalmia" or "moon blindness", is one of the most serious and vision-threatening disorders worldwide. The pathogenesis of the disease is only partially understood, although it is confidently immune mediated, where bacterial {Leptospira, interrogans), viral and parasitic infections, trauma and systemic diseases have been implicated. The clinical manifestations of ERU vary considerably depending on the stage of the disease. The ocular lesions are usually unilateral, whereas in approximately 20% of the cases they are seen in both eyes. Diagnosis is based on ophthalmologic examination along with specific serology, aiming at the detection of any specific infectious agent. Aggressive and early undertaken treatment is of paramount importance in an attempt to preserve vision, decrease ocular pain and prevent or minimize further relapses. The conventional treatment includes the use of glucocorticosteroids or non-steroidal anti-inflammatory drugs along with mydriatics-cycloplegics, while pars plana vitrectomy and cyclosporine A intra-ocular implants may also give encouraging results. Recendy, alternative therapeutic methods (homeopathy, acupuncture) have also been used. Prognosis in ERU is always guarded to poor, because the severity and frequency of the future episodes is unpredictable.